Cost reduction intervention in a commercial restaurant in Fortaleza, Ceará (Research, Society and Development, 2020)
The objective of this study was to evaluate if an educational intervention can reduce the waste of food and indirect expenses in a commercial restaurant, analyzing before and after the educational action. The work was carried out in three moments: Diagnosis, Intervention and Evaluation. At the diagnosis stage, it was observed that 72% of the proteins received in the restaurant had the percentage of melting above the proposed one. Of the total of the leaflets used in the restaurant 50% had the correction factor above the established, and in relation to the verified vegetables, 75%. Regarding indirect costs, habits such as open faucets, lamps and connected equipment, among others, were observed. After the training and corrective actions only 33% of the proteins had the melting index out of acceptable. Regarding the vegetables, mainly the Swiss chard, lettuce and purple lettuce will decrease the correction factor decreased by 19.12%, 19.2% and 18.83 respectively and the vegetables only verified 15.8% did not decrease the correction factors. With regard to energy, water and gas expenses, there was a systematization of the on / off procedures. Although the intervention was short, spending was considerably reduced, resulting in a savings of 17.5%.